EKSISTENSI DAN ESENSI PENDIDIKAN MADRASAH DI INDONESIA - MASKUR, MUHAMMAD (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2017)
Madrasah as an educational institution of Islam has an important role in the  development and progress of the nation. Born from the womb of a boarding school, madrasah have strong religious based traditions and scholarship. The existence of a dichotomy for the sustainability of education in madrasah, is the most obvious challenge to date not yet fully resolved. So the quality of education in madrasah seems to be number two than the education in public schools. The purpose of the establishment of more madrasah to provide tha balance of the world and the hereafter in the life of society with pesantren based education. The rapid development of the age, madrasah must have sensitivity to the situation faced if you do not want eroded by the times with no leave of guidelines and characteristics possessed. The aligment of the interdisiplinary fields with the madrasah body should be strengthened, thus the parents become more convinced with the madrasah. Al-Qur’an as the main basis should be taken seriously by the madrasah. If we see at this time not a few madrasah that have begun to change and shifted from the spirit of boarding school as the forerunner of madrasah. Many ways for madrasah to remain firmly in accordance with the purpose of estabilishment and sensitive to the era, so as not to be left behind. First, hold on to the al-Qur’an; second, reorientation of madrasah education; third, curriculum development; fourth, improvement of madrasah management; fifth, improvement of madrasah leadership; and seventh, increased community participation. Keywords: Existence, essense, madrasah.